2010
DOI: 10.1126/science.1194140
|View full text |Cite
|
Sign up to set email alerts
|

How Learning to Read Changes the Cortical Networks for Vision and Language

Abstract: Does literacy improve brain function? Does it also entail losses? Using functional magnetic resonance imaging, we measured brain responses to spoken and written language, visual faces, houses, tools, and checkers in adults of variable literacy (10 were illiterate, 22 became literate as adults, and 31 were literate in childhood). As literacy enhanced the left fusiform activation evoked by writing, it induced a small competition with faces at this location, but also broadly enhanced visual responses in fusiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

90
965
13
50

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,114 publications
(1,118 citation statements)
references
References 43 publications
90
965
13
50
Order By: Relevance
“…Ziegler and Ferrand (1998) suggest that the mechanisms underlying the effects of orthography on online speech processing are that following literacy training orthographic representations are activated online when processing spoken words and it is such online activation that leads to effects of orthography on speech processing. Neuroimaging evidence consistent with this hypothesis can be found in Dehaene et al (2010) in which online speech processing tasks in literates, but not illiterates, were observed to activate brain regions associated with orthographic processing. However, such evidence is not incompatible with an alternative restructuring hypothesis in which the process of learning orthographic mappings leads to adaptation in other language processing regions.…”
Section: Changes To Phonological Representations and Literacysupporting
confidence: 52%
“…Ziegler and Ferrand (1998) suggest that the mechanisms underlying the effects of orthography on online speech processing are that following literacy training orthographic representations are activated online when processing spoken words and it is such online activation that leads to effects of orthography on speech processing. Neuroimaging evidence consistent with this hypothesis can be found in Dehaene et al (2010) in which online speech processing tasks in literates, but not illiterates, were observed to activate brain regions associated with orthographic processing. However, such evidence is not incompatible with an alternative restructuring hypothesis in which the process of learning orthographic mappings leads to adaptation in other language processing regions.…”
Section: Changes To Phonological Representations and Literacysupporting
confidence: 52%
“…It has been claimed, however, that the dissimilarities seen between the brain responses of dyslexics and controls at school age and as adults could in fact be caused by differences in reading experiences instead of being inherited. Indeed, there is evidence showing that learning to read alters brain activity (Dehaene et al, 2010). On the basis of Studies II and III, and taking into account the earlier findings of the Jyväskylä Longitudinal Study of Dyslexia, an interaction of environmental fac-tors and inherited factors can be seen.…”
Section: The Effect Of Familial Risk On Dyslexiamentioning
confidence: 86%
“…The deficits in higher linguistic processes at sub-lexical and lexical levels have been argued to be a cause for phonological problems and lower-level problems would just co-occur, but not as causal for dyslexia White et al, 2006). Brain research has also shown top-down effects for reading and dyslexia: learning to read has been reported to enhance phonological activation to speech in the planum temporale (Dehaene et al, 2010), with brainlevel abnormalities in the reading network in dyslexics being the consequence of different reading experiences (Clark et al, 2014). However, it is also possible that bottom-up versus top-down effects vary across languages because of the differences in their orthographic transparency.…”
Section: Speech Perception Deficits In Dyslexiamentioning
confidence: 99%
“…Therefore education was controlled as a covariate in our study though it explained comparatively large variance of MoCA. While it is worthy of note that some recent studies suggested the link among the socioeconomic factors including educational level, cerebral white matter integrity and risk of vascular diseases especially stroke in later life [14][15][16]. The underlying mechanisms were assumed that education helped build cortical network and improve cerebral white matter integrity, as well as increase the resistance of central nervous system against impairments.…”
Section: Discussionmentioning
confidence: 99%